Pengaruh Media Sosial dan Literasi Keuangan Terhadap Perilaku Konsumstif Mahasiswa Pendidikan Ekonomi - Rahman, Rahman; Kharisma Nugraha Putra; Hariatama, Fendy (FKIP, Universitas Palangka Raya, 2024)
This research aimed at investigating the effect of social media and financial literacy on consumer behavior of Economics education students of FKIP Palangka Raya University. The research method used in this research is quantitative research method using descriptive approach. The data sources in this study were students of class 2020 and 2021 with a sample of 70 students. The data analysis technique used in this research is the Product Moment Correlation Coefficient analysis method. Based on the results of the study, it is known that social media variables partially contribute more to the variable consumer behavior of students, namely with the value of t count> t table, namely 24.357> 1.669, while financial literacy contributes with the value of t count> t table, namely 3.422> 1.669 Based on simultaneous test data analysis, the value of Fcount> Ftable is obtained, namely 60.997> 3.15 with a significance level of 0.000 (r < 0,05). Based on the value of the coefficient of determination, which is 0.867, meaning that the factor influencing the consumptive behavior of economic education students at FKIP Palangka Raya University is 86.7% contained in social media factors and financial literacy and the remaining 13.3% is influenced by other factors outside this study